2013
DOI: 10.1002/phy2.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for impaired collateral artery growth in the spontaneously hypertensive rat: insight from microarray analysis

Abstract: Analysis of global gene expression in mesenteric control and collateral arteries was used to investigate potential molecules, pathways, and mechanisms responsible for impaired collateral growth in the Spontaneously Hypertensive Rat (SHR). A fundamental difference was observed in overall gene expression pattern in SHR versus Wistar Kyoto (WKY) collaterals; only 6% of genes altered in collaterals were similar between rat strains. Ingenuity® Pathway Analysis (IPA) identified major differences between WKY and SHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Thus, previous studies compared mRNA expression between spontaneously hypertensive rats (SHR) and its normotensive control, the Wistar Kyoto rat (WKY), in kidney [ 2 , 3 ], adrenal gland [ 4 ], vascular smooth muscle cells [ 5 ], and in saphenous arteries[ 6 ]. One study compared collateral resistance arteries from the mesenteric vascular bed of SHR and WKY [ 7 ]. None of these studies included the more recently identified miRNAs, which add another layer of regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous studies compared mRNA expression between spontaneously hypertensive rats (SHR) and its normotensive control, the Wistar Kyoto rat (WKY), in kidney [ 2 , 3 ], adrenal gland [ 4 ], vascular smooth muscle cells [ 5 ], and in saphenous arteries[ 6 ]. One study compared collateral resistance arteries from the mesenteric vascular bed of SHR and WKY [ 7 ]. None of these studies included the more recently identified miRNAs, which add another layer of regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results suggest that mechanisms other than those related to BMDC function may mediate the impaired compensation observed in the presence of some major vascular risk factors. Such mechanisms may include vascular-specific deficits (42) such as dysfunctional nitric oxide signaling (91) and abnormal redox-dependent regulation of gene expression (82). Appropriate antioxidant therapy might also mediate improvement through altered metabolic status (64); however, it has been shown in insulin resistance that vascular function is impaired by Nox2 independent of altered glucose status (75).…”
Section: Discussionmentioning
confidence: 99%
“…The role of NFκB signaling in arteriogenesis has not yet been studied in detail; however, this pathway was found to be continuously activated in situations of disturbed blood flow such as in atherosclerosis [18]. Furthermore, an increase in the nuclear translocation of NFκB and hence an increase in the expression of its target genes was observed in a rat mesenteric model of collateral growth [48]. Moreover, NFκB is also able to induce the expression of VEGF [49], suggesting that there might be an interplay between these two avenues of signaling in mediating the effects of eRNA on endothelial activation during arteriogenesis.…”
Section: Contribution Of Erna In the Promotion Of Collateral Remodelimentioning
confidence: 99%